2019
DOI: 10.1016/j.eurpsy.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-signaling abnormalities in drug-naïve first-episode schizophrenia: Transduction protein analyses in extracellular vesicles of putative neuronal origin

Abstract: Background: Metabolic syndrome and impaired insulin sensitivity may occur as side effects of atypical antipsychotic drugs. However, studies of peripheral insulin resistance using the homeostatic model assessment of insulin resistance (HOMA-IR) or oral glucose tolerance tests (OGTT) suggest that abnormal glucose metabolism is already present in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Studies confirm the occurrence of disorders of glucose homeostasis at the early stages of the disease, such as elevated fasting glucose and insulin, and reduced glucose tolerance [44]. This dysfunction may be associated with neuronal insulin resistance [45]. Glucose is the primary source of energy for the brain and is metabolized to ATP during glycolysis, the electron transport chain (ETC), and included in the tricarboxylic acid cycle (TCA) as presented in Figure 1.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Studies confirm the occurrence of disorders of glucose homeostasis at the early stages of the disease, such as elevated fasting glucose and insulin, and reduced glucose tolerance [44]. This dysfunction may be associated with neuronal insulin resistance [45]. Glucose is the primary source of energy for the brain and is metabolized to ATP during glycolysis, the electron transport chain (ETC), and included in the tricarboxylic acid cycle (TCA) as presented in Figure 1.…”
mentioning
confidence: 90%
“…Modern theories slightly differ from the classical explanations, and assume that in schizophrenic patients, absorption of glucose into brain cells is impaired. That can be associated, (among others), with the wrong concentration of glucose transporters, i.e., GLUT1 and GLUT3, or neuronal insulin resistance [45]. Our preliminary studies on a group of 40 patients with the first episode of psychosis (manuscript in preparation) with the use of magnetic resonance spectroscopy (MRS) showed, that the strongest relationship between the metabolites, i.e., GLU + GLN + GSH 3.7 with positive symptom P scale was observed in a cingulate cortex.…”
mentioning
confidence: 99%
“…In theory, EVs could also be used as therapeutic vehicles, as evidence indicates that their membrane proteins can guide them to specific recipient cells (Van Niel, D'Angelo & Raposo, 2018;Yanez-Mo et al, 2015). To our knowledge, there are only four published studies on psychosis and EVs: one based on brain biopsies (Banigan et al, 2013), a case report involving cerebrospinal fluid (CSF) analysis (Mobarrez et al, 2013), and two studies showing altered insulin signaling in L1 cell adhesion molecule (L1CAM) positive EVs in patients with schizophrenia (Kapogiannis et al, 2019a;Wijtenburg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Du et al validated several distinct miRNAs in serum exosomes, including 11 that could distinguish between the schizophrenia and the control groups (Du et al, 2019). Finally, Kapogiannis et al reported altered expression of proteins relevant to insulin signaling in plasma derived neuronal exosomes from drug naïve first episode schizophrenia patients, suggesting that altered insulin signaling precedes antipsychotic exposure in schizophrenia (Kapogiannis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%